UJI KOMPARASI KUALITAS BERAS VARIETAS PADI SAWAH YANG DIBUDIDAYAKAN SECARA ORGANIK DAN KONVENSIONAL - Achmad Fatchul Aziez; Didik Indradewa; Prapto Yudono; Eko Hanudin (JURNAL ILMIAH AGRINECA, 2016)
Rice quality is the dominant factor of rice. The quality of rice includes the weight percentage of head rice, amylose content and the quality of rice include flavor of rice, rice texture and rice aroma. Rice from different rice varieties will be different quality, so also the way of rice cultivation is also very influential on the quality of rice produced. This study aims to compare the quality of rice from various rice varieties under organically and conventional cultivations. The experiment was conducted on Organic and Conventional rice field in Kebonagung village, Imogiri, Bantul from September 2013 until January 2014 with Inceptisol soil type and altitude of 114 m . This research was designed with Randomized Completely Randomized Block Design which was arranged in a split plot consisting of 2 treatment factors and repeated 4 times. Factor I: Cultivation, namely organic cultivation and conventional cultivation and Factor II kinds of varieties that consist of IR64, Cianjur, Pandanwangi, Mentikwangi and Cisedane. Parameters observed included grain yield, percentage of rice head, amylose content, protein content, and rice quality including rice flavor, rice texture, and rice aroma. The results showed that (1) the yield of grain did not differ between organic cultivation and conventional cultivation. (2) Organic cultivation increased the heavy percentage of rice head of IR64 variety, (3) Organic Cultivation decreased the amylose content of Cianjur and Pandanwangi varieties, and increased the amylopectin level so the rice became more â€œPulenâ€ (4) Organic cultivation raises levels of IR64, Pandanwangi, Mentikwangi and Cisedane variety of varieties, (5) Organic cultivations tend to improve the quality of rice including taste, texture and aroma of rice